La Liga de las Juventudes Comunistas (Komsomol) y la transformación de la Unión Soviética (1917-1932) - Neumann, Matthias (Ariadna Ediciones, 2019)
History of the formation of the komsomol and its inclusion in the new Soviet Stalinist State